Treasures in Islam: The Role of Wealth in the Development of Islamic Business Activities - Mulyono Jamal; Prama Sidiq Ramadhan; zzam Fatahillah Mumtaz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Currently, in the social reality around us, possession of property is considered the standard of one's happiness, and having wealth is considered a sign of good luck. Therefore, it can be considered that the main reason why humans tend to pursue wealth is because of the perception that the need for wealth is comparable to the need for family or descendants. It is best to remember that the wealth in this world basically belongs to Allah SWT, as the Creator and Ruler of the universe and its contents. Therefore, wealth owned by humans should be considered a trust from Allah SWT, and humans are entrusted with managing it responsibly in accordance with the rules contained in the Koran and the teachings of the Prophet Muhammad, both for life in this world and in the afterlife.